Adsorption of fluoride ions on hydroxyapatite-modified Corbula trigona shell waste: Effect of coexisting anions, temperature and regeneration - NZebo YAPO; Kouakou Adou; Judicaël Ano; Dan Nonh; Kouasssi YAO (Journal of Chemistry Letters)
Hydroxyapatite (HAp) synthesized using Corbula trigona shell powder (CTSP) in the presence of 0.3 mol/L phosphoric acid solution was used to evaluate the influence of some parameters such as coexisting anions, temperature and regeneration. Cl- and NO3- ions have no significant effect on fluoride removal efficiency in the studied concentration range while sulfates have a detrimental effect on fluoride removal efficiency. The removal efficiency increases with temperature for all the different concentrations studied (2.2; 5.2; 10.5 and 16.8 mg/L). The thermodynamic results showed that the adsorption process was spontaneous, endothermic and irreversible in nature. The maximum adsorption capacity of fluoride ions was 89.3% in the first cycle and gradually decreased with increasing number of regeneration cycles. HAp could be used up to 5 times during fluoride ion removal with a loss of nearly 56% of its adsorption efficiency. The obtained results showed that HAp derived from Corbula trigona shell waste can be a promising adsorbent for groundwater defluoridation in developing countries.